1985
DOI: 10.1099/00221287-131-3-437
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gramicidin S on the Transcription System of the Producer Bacillus brevis Nagano

Abstract: The effect of the peptide antibiotic gramicidin S, produced by Bacillus brevis Nagano, was tested on the transcription system of the producer by using in vivo, semi in vitro and in vitro systems for studies of RNA synthesis. The effects of other peptide antibiotics (linear gramicidin, tyrocidine and tyrothricin) were also tested for comparison. It was found that (a) RNA polymerase isolated from either gramicidin S-producing or non-producing strains had a similar structure and requirements and that (b) the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Thus, this peptide may be involved in gene regulation during sporulation [ 9 ]. A slightly different result was reported in the case of the peptide antibiotic gramicidin S, as it was observed that gramicidin S did not inhibit transcription during growth and sporulation, but it inhibited transcription during germination and outgrowth [ 10 ]. Sporulation was induced by supplementary peptide antibiotics in B. brevis when the cells were grown under low-nitrogen concentration in the culture medium [ 11 ].…”
Section: Introductionmentioning
confidence: 92%
“…Thus, this peptide may be involved in gene regulation during sporulation [ 9 ]. A slightly different result was reported in the case of the peptide antibiotic gramicidin S, as it was observed that gramicidin S did not inhibit transcription during growth and sporulation, but it inhibited transcription during germination and outgrowth [ 10 ]. Sporulation was induced by supplementary peptide antibiotics in B. brevis when the cells were grown under low-nitrogen concentration in the culture medium [ 11 ].…”
Section: Introductionmentioning
confidence: 92%
“…Gramicidin S interacts with the plasma membrane by forming oligomeric β-barrel pores, which destroys the barrier properties of the membrane [ 56 , 57 ]. Further in vivo studies have shown that gramicidin S binds to the DNA and inhibits transcription and cell growth [ 58 ].…”
Section: Antimicrobial Metabolites and Their Mechanism Of Actionmentioning
confidence: 99%
“…Beyond their antimicrobial activities, the functions of peptide antibiotics in their producers have been the subject of speculation and discussions long before the common master players of these processes became identified [1,2,76,[91][92][93][94]. Function in sporulation, germination and outgrowth have been suggested.…”
Section: Functions Of Bacilysin In Its Producermentioning
confidence: 99%